Utility of Intraoperative 3D TEE to Unmask a Hidden Intracardiac Fistula - Michael Apolinario, MD, MS; Reza Arsanjani, MD; Kristen Sell-Dottin, MD; Chadi Ayoub, MBBS, PhD (JACC: Case Reports)
A 70-year-old woman with a previously repaired atrioventricular septal defect at 8 years of age was found to have severe mitral valve regurgitation in the setting of a mitral valve cleft identified on transesophageal echocardiogram (TEE) and computed tomography imaging. She underwent surgical repair and was found to have an intracardiac shunt on intraoperative TEE that was initially obscured by the severe mitral regurgitant jet. This case highlights the utility of intraoperative 3-dimensional TEE which helped to identify and localize the intracardiac shunt and allowed for appropriate repair of the fistula while patient was still in the operating room.